Integration of Road Roughness Measurement Between Specialized Instrumentation and an Android-Based Application - Lukman, Arbi Parianta; Utami, Retno; Yudhzan, M. Rafli (Institut Teknologi Nasional, Bandung, 2024)
ABSTRAKKeadaan permukaan jalan sangat penting untuk menjamin keamanan dan kenyamanan pengguna jalan. Menjaga kondisi jalan agar tetap aman dan nyaman merupakan hal krusial karena jalan adalah infrastruktur vital dalam transportasi orang dan barang. Untuk memperbaiki infrastruktur transportasi, evaluasi kondisi jalan sangat diperlukan. Salah satu pendekatan umum adalah dengan mengukur kekasaran jalan, yang sering dilakukan dengan perangkat seperti Roughometer III dan aplikasi Roadroid berbasis smartphone. Penelitian ini bertujuan membandingkan nilai International Roughness Index (IRI) yang diperoleh dari kedua perangkat tersebut pada perkerasan kaku di jalan tol. Pengujian dilakukan sepanjang 10 kilometer, dengan pengukuran nilai IRI setiap 10 meter. Hasil pengujian menunjukkan bahwa perangkat Roughometer III dan Roadroid dipasang pada kendaraan yang sama. Analisis hubungan antara nilai IRI dari kedua perangkat menggunakan analisis polinomial menghasilkan persamaan IRI (Roughometer) = -0,0022(IRIrd)² + 0,8464(IRIrd) + 1,8894, dengan koefisien determinasi (R²) sebesar 0,47. Kata kunci: Internasional roughness indeks, Roughometer III, Roadroid, Evaluasi Perkerasan. ABSTRACTThe condition of road pavement surfaces is crucial for ensuring the safety and comfort of road users. Proper maintenance of road conditions is essential as roads serve as vital infrastructure for transporting people and goods. Evaluating road conditions is therefore critical for improving transportation infrastructure. Road roughness measurements are the most common method used by road managers to assess pavement surfaces. This study aims to compare the International Roughness Index (IRI) values obtained using the Roughometer III device with those obtained using the smartphone-based Roadroid application. Testing was conducted on a 10-kilometer stretch of rigid pavement on a toll road. IRI values were measured every 10 meters. The Roughometer III and Roadroid devices were tested on the same vehicle. A polynomial analysis was performed to determine the relationship between the IRI values from both devices, resulting in the equation IRI (Roughometer) = -0.0022(IRIrd)² + 0.8464(IRIrd) + 1.8894, with a coefficient of determination (R²) of 0.4701.Keywords: Internasional Roughness Index, Roughometer III, Roadroid, Pavement Evaluation.